Intensive measurements of gas, water, and energy exchange between vegetation and troposphere during the MONTES Campaign in a vegetation gradient from short semi-desertic shrublands to tall wet temperate forests in the NW Mediterranean basin - Penuelas, J; Guenther, A; Rapparini, F; Llusia, J; Filella, I; Seco, R; Estiarte, M; Mejia-Chang, M; Ogaya, R; Ibáñez, J; Sardans, J; Castaño, L M; et al. (Atmospheric Environment)
Abstract MONTES (“Woodlands”) was a multidisciplinary international field campaign aimed at measuring energy, water and especially gas exchange between vegetation and atmosphere in a gradient from short semi-desertic shrublands to tall wet temperate forests in NE Spain in the North Western Mediterranean Basin (WMB). The measurements were performed at a semidesertic area (Monegros), at a coastal Meditrerranean shrubland area (Garraf), at a typical Mediterranean holm oak forest area (Prades) and at a wet temperate beech forest (Montseny) during spring (April 2010) under optimal plant physiological conditions in driest-warmest sites and during summer (July 2010) with drought and heat stresses in the driest-warmest sites and optimal conditions in the wettest-coolest site. The objective of this campaign was to study the differences in gas, water and energy exchange occurring at different vegetation coverages and biomasses. Particular attention was devoted to quantitatively understand the exchange of biogenic volatile organic compounds (BVOCs) because of their biological and environmental effects in the WMB. A wide range of instruments (GC-MS, PTR-MS, meteorological sensors, O3 monitors,…) and vertical platforms such as masts, tethered balloons and aircraft were used to characterize the gas, water and energy exchange at increasing footprint areas by measuring vertical profiles. In this paper we provide an overview of the MONTES campaign: the objectives, the characterization of the biomass and gas, water and energy exchange in the 4 sites-areas using satellite data, the estimation of isoprene and monoterpene emissions using MEGAN model, the measurements performed and the first results. The isoprene and monoterpene emission rates estimated with MEGAN and emission factors measured at the foliar level for the dominant species ranged from about 0 to 0.2 mg m-2 h-1 in April. The warmer temperature in July resulted in higher model estimates from about 0 to ca 1.6 mg m-2 h-1 for isoprene and ca. 4.5 mg m-2 h-1 for monoterpenes, depending on the site vegetation and footprint area considered. There were clear daily and seasonal patterns with higher emission rates and mixing ratios at midday and summer relative to early morning and early spring. There was a significant trend in CO2 fixation (from 1 to 10 mg C m-2 d-1), transpiration (from x 1 to 5 kg C m-2 d-1), and sensible and latent heat from the warmest-driest to the coolest-wettest site. The results showed the strong land-cover-specific influence on emissions of BVOCs, gas, energy and water exchange, and therefore demonstrate the potential for feed-back to atmospheric chemistry and climate.
Keywords: aircraft; Boundary Layer; CH4; CO2; Evapotranspiration; green biomass; isoprene; lai; Land Cover; latent heat; masts; MEGAN; Monoterpenes; N2O; NDVI; O3; sensible heat; tethered balloons; Vegetation; vertical profiles; VOCs

Changes in DNA methylation fingerprint of Quercus ilex trees in response to experimental field drought simulating projected climate change - Rico, L; Ogaya, R; Barbeta, A; Penuelas, J (Plant Biology, 2014)
Rapid genetic changes in plants have been reported in response to current climate change. We assessed the capacity of trees in a natural forest to produce rapid acclimation responses based on epigenetic modifications. We analysed natural populations of Quercus ilex, the dominant tree species of Mediterranean forests, using the methylation-sensitive amplified polymorphism (MSAP) technique to assess patterns and levels of methylation in individuals from unstressed forest plots and from plots experimentally exposed to drought for 12 years at levels projected for the coming decades. The percentage of hypermethylated loci increased, and the percentage of fully methylated loci clearly decreased in plants exposed to drought. Multivariate analyses exploring the status of methylation at MSAP loci also showed clear differentiation depending on stress. The PCA scores for the MSAP profiles clearly separated the genetic from the epigenetic structure, and also significantly separated the samples within each group in response to drought. Changes in DNA methylation highlight the large capacity of plants to rapidly acclimate to changing environmental conditions, including trees with long life spans, and our results demonstrate those changes. These changes, although unable to prevent the decreased growth and higher mortality associated with this experimental drought, occurred together with a dampening in such decreases as the long-term treatment progressed.
Keywords: climate change; DNA methylation; Drought; methylation-sensitive amplified polymorphism

Community structures of N-2-fixing bacteria associated with the phyllosphere of a Holm oak forest and their response to drought - Rico, L; Ogaya, R; Terradas, J; Penuelas, J (PLANT BIOLOGY, 2014)
Biological nitrogen (N) fixation is a key pathway in terrestrial ecosystems and is therefore critical for understanding the responses of ecosystems to global environmental changes. The free-living diazotrophic community is distributed along the canopy-to-soil profile, but the ecological significance of epiphyllic N-2 fixers, despite their functional relevance, on plant foliar surfaces remains very poorly understood compared with the N-2-fixing community in forest litter and soils. We assessed the community structure of N-2 fixers and overall bacteria by genetic fingerprinting (t-RFLP) to explore the seasonal successional patterns of the microbial community in the natural phyllosphere of a Holm oak (Quercus ilex) forest submitted to 12-year field experiment of rain exclusion mimicking the conditions of drought projected for the coming decades. Leaves of Holm oak were analysed in different seasons over a period of 1.5years. The bacterial community of the phyllosphere did not correspond to the surrounding soil biome in the same area. These analyses provided field evidence for the presence of free-living diazotrophs associated with the tissues of leaves of Holm oak, the dominant tree species of many Mediterranean forests. The results also revealed that the community composition is affected seasonally and inter-annually by the environment, and that the composition shifts in response to climate change. Drought treatment increased the richness of the epiphyllic microbial community, especially during the summer. These changes were associated with higher C:N ratios of leaves observed in response to drought in semiarid areas. This epiphyllic microbiota that can potentially fix N-2 extends the capacity of plants to adapt to the environment.
Keywords: Bacterial TRF richness; diazotrophic community; Drought; foliar phyllosphere; Quercus ilex; t-RFLP; Trees

Strong functional stability of soil microbial communities under semiarid Mediterranean conditions and subjected to long-term shifts in baseline precipitation - Curiel Yuste, J; Fernandez-Gonzalez, a.J. J; Fernandez-Lopez, M; Ogaya, R; Penuelas, J; Sardans, J; Lloret, F (Soil Biology and Biochemistry, 2014)
Abstract We investigated the effect of soil microclimate on the structure and functioning of soil microbial communities in a Mediterranean Holm-oak forest subjected to 10 years of partial rain exclusion manipulations, simulating average drought conditions expected in Mediterranean areas for the following decades. We applied a high throughput DNA pyrosequencing technique coupled to parallel measurements of microbial respiration (RH) and temperature sensitivity of microbial respiration (Q10). Some consistent changes in the structure of bacterial communities suggest a slow process of community shifts parallel to the trend towards oligotrophy in response to long-term droughts. However, the structure of bacterial communities was mainly determined by short-term environmental fluctuations associated with sampling date (winter, spring and summer) rather than long-term (10 years) shifts in baseline precipitation. Moreover, long-term drought did not exert any chronic effect on the functioning of soil microbial communities (RH and Q10), emphasizing the functional stability of these communities to this long-term but mild shifts in water availability. We hypothesize that the particular conditions of the Mediterranean climate with strong seasonal shifts in both temperature and soil water availability but also characterized by very extreme environmental conditions during summer, was acting as a strong force in community assembling, selecting phenotypes adapted to the semiarid conditions characterizing Mediterranean ecosystems. Relations of climate with the phylogenetic structure and overall diversity of the communities as well as the distribution of the individual responses of different lineages (genera) to climate confirmed our hypotheses, evidencing communities dominated by thermotolerant and drought-tolerant phenotypes.
Keywords: Adaptation; CO2; diversity; Extreme events; functional stability; Mediterranean climate; Soil bacterial communities

Summer season and long-term drought increase the richness of bacteria and fungi in the foliar phyllosphere of Quercus ilex in a mixed Mediterranean forest - Penuelas, J; Rico, L; Ogaya, R; Jump, A S; Terradas, J (Plant Biology, 2012)
We explored the changes in richness, diversity and evenness of epiphytic (on the leaf surface) and endophytic (within leaf tissues) bacteria and fungi in the foliar phyllosphere of Quercus ilex, the dominant tree species of Mediterranean forests. Bacteria and fungi were assessed during ontogenic development of the leaves, from the wet spring to the dry summer season in control plots and in plots subjected to drought conditions mimicking those projected for future decades. Our aim was to monitor succession in microbiota during the colonisation of plant leaves and its response to climate change. Ontogeny and seasonality exerted a strong influence on richness and diversity of the microbial phyllosphere community, which decreased in summer in the whole leaf and increased in summer in the epiphytic phyllosphere. Drought precluded the decrease in whole leaf phyllosphere diversity and increased the rise in the epiphytic phyllosphere. Both whole leaf bacterial and fungal richness decreased with the decrease in physiological activity and productivity of the summer season in control trees. As expected, the richness of epiphytic bacteria and fungi increased in summer after increasing time of colonisation. Under summer dry conditions, there was a positive relationship between TRF (terminal restriction fragments) richness and drought, both for whole leaf and epiphytic phyllosphere, and especially for fungal communities. These results demonstrate that changes in climate are likely to significantly alter microbial abundance and composition of the phyllosphere. Given the diverse functions and large number of phyllospheric microbes, the potential functional implications of such community shifts warrant exploration.
Keywords: Bacteria; Bacteria: genetics; Bacteria: growth & development; Bacterial; Bacterial TRF richness; Bacterial: genetics; Biodiversity; colonisation time; DNA; Drought; Droughts; endophytes; epiphytes; foliar and epiphytic microbial diversity; foliar phyllosphere; Fungal; fungal TRF richness; Fungal: genetics; fungi; Fungi: genetics; Fungi: growth & development; Mediterranean Region; Plant Leaves; Plant Leaves: microbiology; Polymorphism; Quercus; Quercus: microbiology; Restriction Fragment Length; Seasonality; Seasons; Trees; Trees: microbiology

Species-specific, seasonal, inter-annual, and historically-accumulated changes in foliar terpene emission rates in Phillyrea latifolia and Quercus ilex submitted to rain exclusion in the Prades Mountains (Catalonia) - Llusia, J; Penuelas, J; Alessio, G a.; Ogaya, R (Russian Journal of Plant Physiology, 2011)
Mediterranean vegetation emits large amounts of terpenes. We aimed to study the effects of the decreases in soil water availability forecast for the next decades by global circulation models and ecophysio logical models on the terpene emissions by two widely distributed Mediterranean woody species, Phillyrea latifolia L. and Quercus ilex L. We subjected holm oak forest plots to an experimental soil drought of ca. 20% decrease in soil moisture by partial rainfall exclusion and runoff exclusion. We measured the emission rates throughout the seasons for two years with contrasting precipitation and soil moisture (16.6% average in 2003 vs. 6.4% as average in 2005). Among the detected volatile terpenes, only αpinene and limonene were present in detectable quantities in all of the studied periods. Total terpene emitted ranged from practically zero (spring 2003) to 3.6 and 58.3 μg/(g dry wt h) (winter 2005 and summer 2003 for P. latifolia and Q. ilex, respec tively). A clear seasonality was found in the emission rates (they were the highest in summer in both species) and also in the qualitative composition of the emission mix. Maximum emissions of αpinene occurred in spring and maximum emissions of limonene in winter. Neither the interannual differences in water availabil ity nor the rain exclusion treatment significantly affected the emissions in P. latifolia, but Q. ilex showed by 17% lower emissions during the drier second year of study, 2005, but more than two and threefold increases with the drought treatment in summer 2003 and in summer 2005, respectively, showing historical accumu lated effects. These results, which show increased monoterpene emission under the moderate drought pro duced by the treatment and decreased emission under the severe second year drought, and a much higher sen sitivity to drought in Q. ilex than in P. latifolia, are useful in understanding the behavior of plant volatiles under Mediterranean conditions and in modeling future emission under changing climate conditions. They show that the usage of current models could lead to under and overestimations of the emission under summer dry conditions, because most current algorithms are based on light and temperature only.
Keywords: isoprenoid emission; Monoterpenes; phillyrea latifolia; Quercus ilex; water stress

Influence of water and terpenes on flammability in some dominant Mediterranean species - Alessio, G A; Penuelas, J; Llusia, J; Ogaya, R; Estiarte, M; De Lillis, M (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2008)
In the Mediterranean basin, fires are a major concern for forest and shrubland ecosystems. We studied flammability, its seasonality and its relationship with leaf moisture and volatile terpene content and emission in the dominant species of a Mediterranean shrubland and forest in Catalonia ( NE Iberian Peninsula). We measured temperatures and time elapsed between the three flammability phases: smoke, pyrolysis and flame, for four seasons. We sampled twice in spring because of an occasional drought period during this season. Flammability had a significant relationship with leaf hydration, in the shrubland and in the forest. Few and only weak correlations were found between terpene content and flammability. In the future, arid conditions projected by climatic and ecophysiological models will increase fire risk through decreased hydration and subsequent increased flammability of the species.
Keywords: Arbutus unedo; Cistus albidus; emission and content of volatile compounds; Erica multiflora; Globularia alypum; phillyrea latifolia; Pinus halepensis; Pistacia lentiscus; Quercus ilex; Rosmarinus officinalis

Seasonal soil VOC exchange rates in a Mediterranean holm oak forest and their responses to drought conditions - Asensio, D; Penuelas, J; Ogaya, R; Llusia, J (Atmospheric Environment, 2007)
Available information on soil volatile organic compound (VOC) exchange, emissions and uptake, is very scarce. We here describe the amounts and seasonality of soil VOC exchange during a year in a natural Mediterranean holm oak forest growing in Southern Catalonia. We investigated changes in soil VOC dynamics in drought conditions by decreasing the soil moisture to 30% of ambient conditions by artiﬁcially excluding rainfall and water runoff, and predicted the response of VOC exchange to the drought forecasted in the Mediterranean region for the next decades by GCM and ecophysiological models. The annual average of the total (detected) soil VOC and total monoterpene exchange rates were 3.273.2 and 0.470.3 mg m 2 h 1 , respectively, in control plots. These values represent 0.003% of the total C emitted by soil at the study site as CO2 whereas the annual mean of soil monoterpene exchange represents 0.0004% of total C. Total soil VOC exchange rates in control plots showed seasonal variations following changes in soil moisture and phenology. Maximum values were found in spring (1778 mg m 2 h 1 ). Although there was no signiﬁcant global effect of drought treatment on the total soil VOC exchange rates, annual average of total VOC exchange rates in drought plots resulted in an uptake rate (0.571.8 mg m 2 h 1 ) instead of positive net emission rates. Larger soil VOC and monoterpene exchanges were measured in drought plots than in control plots in summer, which might be mostly attributable to autotrophic (roots) metabolism. The results show that the diversity and magnitude of monoterpene and VOC soil emissions are low compared with plant emissions, that they are driven by soil moisture, that they represent a very small part of the soil-released carbon and that they may be strongly reduced or even reversed into net uptakes by the predicted decreases of soil water availability in the next decades. In all cases, it seems that VOC ﬂuxes in soil might have greater impact on soil ecology than on atmospheric chemistry
Keywords: climate change; Drought; Mediterranean holm oak forest; Monoterpenes; Soil CO2 flux; Soil VOC exchange

Estimation of plant water concentration by the reflectance Water Index WI (R900/R970) - Penuelas, J; Piñol, J; Ogaya, R; Filella, I (International Journal of Remote Sensing, 1997)
Abstract Water Index WI (R900/R970) was used for the estimation of plant water concentration (PWC) by ground-based, reflectance measurements. Reflectance and PWC were measured for adult plants growing in the field throughout an annual cycle and in potted seedlings submitted to progressive desiccation. The species studied were characteristicly Mediterranean: Pinus halepensis, Quercus ilex, Quercus coccifera, Arbutus unedo, Cistus albidus, Cistus monspeliensis, Phillyrea angustifolia, Pistacia lentiscus and Brachypodium retusum . WI was significantly correlated with PWC when all the species were considered together, and with almost all the species considered individually, especially when a wider range of PWC was obtained by extreme dessication of experimental plants. The correlations increased when normalizing WI by NDVI. The wavelength of the trough corresponding to water absorption band tended to shift from 970-980 nm to lower wavelengths 930-950 nm with decreasing PWCs. Infrared measurement of plant temperature and T leaf - T air provided worse assessment of PWC. A simple radiometer measuring plant reflectance at 680, 900, and 970nm could speed up the measurement of PWC, and be useful in wildfire risk evaluation and drought assessment.
doi: 10.1080/014311697217396
Keywords: Mediterranean plant species (voyant); NDVI; plant water concentration (PWC); water index